Evaluation of Care General Insurance System Solution Using the Delone and Mclean Methods at XYZ Insurance - Andry Leonardo Hutagaol*; Sfenrianto Sfenrianto (Universitas Syiah Kuala, 2023)
Along with the vision and mission set in the organization or company and supported by rapid technological developments, XYZ Insurance must be able to balance its business strategy with information technology to carry out currently developing business processes. Information systems are required to become an integrated system that can achieve the highest point of effectiveness and efficiency, and assist complex business activities. The purpose of this study is to test how successful the implementation of the CGISS system is at XYZ Insurance by using DeLone and McLean variables including: Information Quality, System Quality, Service Quality, Use, User Satisfaction, Net Benefit, as well as two additional variables from UTAUT namely Performance Expectancy and Effort Expectancy. The population taken is all internal employees of XYZ Insurance head office and branch offices who have email addresses with xyz insurance domains and some samples needed for this case study of 100 samples to examine respondents' views based on variables: System Quality, Information Quality, Service Quality, Intention to Use/Use, User Satisfaction Performance Expectations, Effort Expectations, and Net Benefit. Some of the variables involved in this research include having several influences on the CGISS application. Identification of various obstacles/problems encountered so far can be used as a reference for improving and enhancing the performance of CGISS applications in the future. The results of data processing show that the 7 rejected hypotheses have no significant effect on the use of the CGISS application and 4 of the 11 hypotheses are considered proven that user satisfaction is strongly influenced by two main factors as follows: information quality and service quality. Managerial implications that can be carried out by XYZ Insurance internal parties regarding the CGISS Application as an internal activity information system at XYZ Insurance. This research can be used as material for consideration and evaluation regarding motivation, opportunities, processes, problems, and the performance of application managers so far.